Design and Optimization of an Active OTA-C Filter Based on STOHE Algorithm - Barri D.; Jakovenko J. (University of West Bohemia, 2019)
With increasing demands on design and optimization of analog circuits in real applications, a limited number of algorithms for practical use have been presented. The drawbacks of already existing standard algorithms are in a possibility to stagnate in a not optimal solution and also big time consumption. These drawbacks have been overcome by our new proposed algorithm STOHE. The new algorithm is a combination of a STOchastic and HEuristic algorithms. As the stochastic respectively heuristic algorithm was chosen differential evolution algorithm respectively simplex algorithm. The algorithm has been verified by the design and optimization of an active OTA-C filter where the standard approach fails.
Keywords: differential evolution algorithm; OTA-C filter; simplex algorithm; STOHE algorithm